The Influence of Slow Deep Breathing Technique on Inpatient Anxiety - Nusa Harta, I Putu Arika; Kamaryati, Ni Putu; Putra, I Nyoman Arya Maha; Wicaksana, IGA Tresna (Babali Nursing Research, 2023)
Previous studies have shown that slow deep breathing techniques provide benefits in reducing anxiety in general, but there has been no specific review investigating its benefits in inpatient populations. Objective: To provide strong and up-to-date evidence on the effectiveness of slow deep breathing technique as a potential intervention in reducing anxiety in the inpatient population. Methods: This study is a literature review conducted during April-May 2023 using Google Scholar, PubMed, and ScienceDirect. The keywords used were "nafas dalam", "kecemasan", "rawat inap" in Indonesian, and "slow deep breathing," "anxiety," "inpatient care" in English. Results: The literature review identified eight articles that examined the anxiety of patients undergoing surgery and treatment in hospitals in Indonesia. These articles highlighted internal and external factors influencing anxiety. The dominant research approach employed experimental designs with pre-test and post-test measurements involving more than ten respondents. The study found that internal factors influencing anxiety included age, gender, education, health condition, and prior hospitalization experiences, while external factors included access to information, therapeutic communication, environment, and healthcare facilities. Conclusion: The implementation of slow deep breathing techniques is a major factor in reducing anxiety in inpatient populations. Further research is expected to emphasize the use of slow deep breathing techniques as a primary intervention in reducing anxiety levels in patients prior to undergoing surgery.